Determination of sotolon content in South African white wines by two novel HPLC–UV and UPLC–MS methods. (15th February 2015) - Gabrielli, Mario; Buica, Astrid; Fracassetti, Daniela; Stander, Marietjie; Tirelli, Antonio; du Toit, Wessel J.
Highlights: Novel UPLC and HPLC methods for sotolon analyses in wine. Method is rapid with low detection limits. Sotolon levels in South African wines in most cases lower than sensory perception. Abstract: Sotolon has been reported to play an important role in the atypical ageing and aroma character of many wines. A number of analytical techniques for sotolon analysis in wine have been reported, but these often require extensive sample preparation. In this work we report a HPLC–UV method and a novel UPLC–MS method to determine sotolon concentrations in white wines with little sample preparation applied for the first time for the evaluation of sotolon levels in South African wines. The validation showed that the instrumental methods had good accuracy, repeatability and linearity, but the UPLC–MS method proved more sensitive. For both methods, quantification limits were lower than the sotolon odour threshold in wine (10 μg/L), 0.86 μg/L and 0.013 μg/L, for HPLC–UV and UPLC–MS methods, respectively. Sotolon levels in 65 South African white wines were often found to be lower than the reported odour threshold, with the highest concentration being 9.11 μg/L. However, for low levels (<1 μg/L), unknown interferences in certain wines led to sotolon not being quantified with the HPLC–UV method, which made the UPLC–MS method more suitable.